Impact of Liberalization Policies on Indian Economy: Analyzing the Impact of Liberalization Policies on the Indian Manufacturing Sector (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The economic reforms and liberalization adopted by Indiasince 1991 have affected the Indian economy in general and manufacturing sectorin particular in a number of ways. There is no dearth of literature on studiesrelated with performance of manufacturing sector in India. However, very fewstudies have been conducted to segregate the impact of liberalization policieson economy in terms of efficiency and market conditions. In the present study,an attempt will be made to analyze the manufacturing sector of India atindustry level with particular emphasis at impact of liberalization on growth,productivity, profitability, employment and wages.